Using strip seeding to test how restoration design affects randomness of community assembly. Issue 6 (21st June 2019) - Gornish, Elise S.; Shaw, Julea; Gillespie, Breahna M.
Abstract : The reestablishment and enhancement of plant diversity is typically a priority for restoration practitioners. Since diversity and stability can be affected by the magnitude to which randomness drives community dynamics, modifying randomness (via habitat heterogeneity) could provide utility for vegetation managers. We investigated the value of using strip seeding to manipulate the magnitude to which randomness structures plant communities across a grassland in Davis, California. Five years after restoring portions of a degraded site (0, 33, 50, 66, and 100% of an area) to create patches of seeded and unseeded strips, we assessed the amount of Jaccard dissimilarity across quadrats within strips and estimated the magnitude to which randomness contributed to community assembly (termed the nugget). We found higher nuggets in the 66 and 33% seeding treatment levels compared to the 0, 50, and 100% seeding treatment levels. In the 33 and 66% level of the seeding treatment, we also found that unseeded strips, which are regularly exposed to random events of dispersal from seeded strips, had a higher nugget than seeded strips. This work suggests that strategic seeding techniques that enhance habitat heterogeneity can increase the role of randomness in community dynamics. Strip seeding strategies appear to provide utility as a tool to indirectly enhance diversity across a degraded site.